Improving Functioning of Children Birth to Five with Emotional and Behavioral Problems: The Role of Comprehensive Mental Health Services and Supports - Alison K. Cohen; Tracy Hazelton; Henrissa Bassey; Margie Gutierrez-Padilla; Carolyn Novosel; Chloe R. Nichols; Sonia Jain (MDPI AG, 2023)
Introduction: Emotional and behavioral problems are growing among children ages birth to five, and racial/ethnic and socioeconomic disparities exist. Comprehensive, culturally responsive, family-driven systems of care, such as the one operated by California's diverse, urban Alameda County, offer one potential intervention. Methods: We used client-level service data (n = 496 children) to calculate descriptive statistics and regression analyses (including multilevel models to account for observations for the same client at multiple points in time). We estimated the prevalence of mental health issues and assessed the association between the length of time using services and emotional and behavioral functioning. Results: Comprehensive mental health services and supports were associated with improved emotional and behavioral functioning outcomes for children over time, even after controlling for other risk factors. Discussion: Systems of care appear to support the multidimensional functioning of children and their families.